Inspiring aspirations: an interpretative phenomenogical analysis and exploration of aspiration development in looked after children and young people - Perry-Springer, Michéle A. (2016)
Government data continues to indicate that Looked After Children and Young People (LAC/YP) are vulnerable to poor academic achievement and later life outcome. Over the years successive Governments have legislated and invested in policy changes and guidance to inform practice in an effort to close the academic and social gap between those young people in care and their non-looked after peers. The espoused target for intervention and change has been with regards to raising the aspirations of LAC/YP. Seven LAC/YP were interviewed in order to capture their views about their future aspirations and for their perspectives on the factors in their lives that they identified as helping or hindering them as they constructed their future selves. Interpretative Phenomenological Analysis (IPA) methodology was used to better understand some of the lived experiences of the LAC/YP within the system aimed to raise their aspirations. Super-ordinate themes of ‘Imagined future’, ‘Current Support’, ‘Personal sense of agency’ and ‘Impact of past care’ emerged from the data. The implications for policy and practice are discussed in light of the challenges in generalising findings from IPA studies beyond the idiographic.